Does Competition Improve Analysts’ Forecast Informativeness? - Banerjee, Sanjay (Management Science, 2021)
This paper studies the effect of competition on analysts’ forecast informativeness. Analysts compete to achieve a higher rank in forecast accuracy. Competition can impair, improve, or have no effect on analysts’ forecast informativeness. Competition impairs informativeness if and only if the prior uncertainty of the economic state is high, and analysts’ private signals are positively correlated conditional on the state. The more intense the competition in terms of a higher prize-to-penalty ratio and a stronger signal correlation, the less informative the forecasts. The higher the number of competing analysts, the greater the likelihood that analyst forecasts are less informative. This paper was accepted by Suraj Srinivasan, accounting.